On completeness of integral manifolds of nullity distributions - Vittone, Francisco (2012)
We give a conceptual proof of the fact that if M is a complete submanifold of a space form, then the maximal integral manifolds of the nullity distribution of its second fundamental form through points of minimal index of nullity are complete.